DAMPAK ERA GLOBALISASI DI PENDIDIKAN (PENDIDIK DAN PESERTA DIDIK) - Nasrul Fauzi; M Averros Azzam Al Islami (MISOOL: Jurnal Pendidikan Dasar, 2020)
Globalization is a global process. Globalization affects almost all aspects of life, and can not be avoided both positive and negative effects, especially on education. So that educators must be more professional and creative, students who master technology from an early age. The purpose of this study is to find out how the influence of globalization on educators and students. The method used is the method of literature study (literatus) and documentation. The results of this study are that globalization has brought changes to all aspects of life, especially in the world of education. Globalization can have both positive and negative impacts on the world of education. It has a positive impact if it makes changes that bring Indonesian education to a more advanced direction, and a negative impact if it reduces the quality of education itself. In the era of globalization, teachers also play an important role in developing students. Teachers not only give lessons but also develop the character of students in a professional and quality era. In addition, as a teacher, you must have good ethics and noble character so that you can set an example for students. In the era of globalization, teachers must be able to provide good teaching to their students. In the era of globalization, teachers must be able to face challenges, namely by providing orientation, not theories but practice to create learning that will later form an independent character in students for future provisions